A human genome-wide loss-of-function screen identifies effective chikungunya antiviral drugs - Alexander Karlas (Nature Portfolio, 2016)
Chikungunya virus is a mosquito transmitted untreatable emergent pathogen that causes joint pain and fever. Here the authors perform a host genome-wide loss-of-function screen to identify targets for chikungunya antiviral drugs and validate hits using a mouse model of chikungunya infection.